Date (Phoenix dactylifera L.) Fruits as a Potential Lipid-Lowering Therapy: Effect on High-Fat Diet and Triton-WR-1339-Induced Hyperlipidemic Rats - Eimad Dine Tariq Bouhlali; Abdelbassat Hmidani; Bouchra Bourkhis; Zineb Moussafir; Younes Filali-Zegzouti; Chakib Alem (Drugs and Drug Candidates, 2023)
The present study was designed to establish the phenolic profile and explore the potential lipid-lowering effect of two Moroccan date fruit varieties (Majhoul and Bousrdoun). HPLC-DAD has been used for phenolic profiling. Lipid peroxidation was measured in terms of thiobarbituric acid-reactive substances (TBARS) by using egg yolk homogenate as lipid-rich media. The anti-hyperlipidemic effect of the methanolic extract was examined using both models Triton-WR-1339 and chronic high-fat-diet-induced hyperlipemic rats. Further, the serum lipid profile was determined. The HPLC-DAD analysis revealed the presence of seven phenolic acids and three flavonoids, of which gallic, caffeic acids and rutin were found to be the most abundant compounds. The gathered results indicate that rats treated with both varieties showed a significant decrease in serum total cholesterol, triglycerides, and low-density lipoprotein cholesterol levels as well as an increase in high-density lipoprotein cholesterol levels compared with Triton and high-fat diet controls. Moreover, a significant decrease in body weight was observed in the date-treated groups when compared to the hyperlipidemic control group. A thiobarbituric acid reactive substances test showed that these extracts significantly inhibited lipid peroxidation. Bousrdoun, which showed the highest lipid-lowering effects, is the one that displayed the greatest inhibition of lipid peroxidation and contains the largest amount of caffeic, p-coumaric, gallic, vanillic acids, rutin and luteolin. Accordingly, dates could be used as a potential functional food, which may be used to prevent lipid disorders and oxidation.